Clinical Characteristics of the SARS-CoV-2 Alpha, Delta, Delta plus and Omicron Variants versus the Wild Type in Iraqi Patients - Salah, Khadija Th.; Fadhil, Hula Y. (Iraqi Journal of Science, 2023)
Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome called coronavirus 2 (SARS-CoV-2). Due to its concerning rate of transmission and intensity, coronavirus was classified as a pandemic on March 11, 2020. With the continuous evolution of the viral genome and mutations that may alter infectivity, disease severity or interactions with host immunity, SARS-CoV-2 has evolved into many variants: Alpha (B.1.1.7 lineage), Delta (B.1.617.2 lineage), Delta plus (B.1.617.2.1), Omicron (B.1.1.529 lineage) and other variants. Thus, this study aimed to find and provide database for local clinical characteristics of different variants of SARS-COV-2 and severity of infection with viral load compared with the wild type. A total of 247 nasal swabs were collected from COVID-19 positive patients between March 2021 to March 2022. Specimens were tested by using real time reverse transcriptase polymerase chain reaction rRT-PCR assay to confirm the infection after RNA extraction by specialized kits. Results showed Alpha, Delta, Delta plus and Omicron variants presence in local population at the same time of their global spread at high rates with different cases of severity. The finding showed increase in severity with Alpha 79/87 (90%), wild type 26/32 (81%) (with 3 mortality cases), Delta/ Delta plus 68/84 (80%) and Kappa only one case. Also, Alpha along with the wild type was more associated to severe and critical cases, while mild to moderate group appeared with Omicron variant (32/43 (74%)). In addition, there was an increase in the severity among older patients (>40) and in men more than the women. Results indicate that although the wild type was no less dangerous or severe than Alpha or other variants, but with continuous appearence of new variants led to its reduced prevalence. In conclusion, findings demonstrated that most of the severe and critical cases had infection with Alpha, wild type than Delta or Delta plus variants. Whereas mild to moderate cases occurred in Omicron variants.